A Novel Strong and Ductile TWIP/Martensite Steel Composite1. Issue 1 (8th May 2015) - Bouaziz, O.; Masse, J. P.; Petitgand, G.; Huang, M. X.
Abstract : A novel bi‐layered steel composite consisting of a martensitic steel and a high manganese twinning‐induced plasticity (TWIP) steel has been fabricated by roll bonding at high temperature. Microstructural and mechanical characterizations highlight that the presented bi‐layered steel composite exhibits simultaneously a high yield stress and high uniform elongation, as both the advantages of TWIP steel and martensitic steel are inherited. Abstract : A bi‐layered steel composite consisting of a martensitic steel and a twinning‐induced plasticity (TWIP) steel is fabricated by roll bonding. The steel composite possesses the advantages of TWIP (high ductility) and martensitic steels (high yield stress) so that it has simultaneously high yield stress and high uniform elongation.